Effect of extrinsic pigmentation and multiple firing cycles on the properties of a zirconia-containing lithium silicate ceramic - Andrade, Everton Cocati (2025)
Purpose: To assess the impact of staining and multiple firings on the mechanical, optical, and surface characteristics of zirconia-containing lithium silicate ceramics (ZLS). Materials and Methods: Ninety ZLS discs (Suprinity, VITA Zahnfabrick) were divided according to the “Number of firings” protocol: Ctr-control, no characterization; SC–single firing cycle (for characterization, crystallization and staining simultaneously); and DC–double firing cycle (crystallization firing cycle was performed separately from the staining firing). Extrinsic pigmentation was performed to replicate the characterization of a monolithic restoration. A layer of stain and glaze was applied with a fine brush to the ceramic surface. Specimens were fired two or four cycles, designed to simulate additional staining firings for potential characterization adjustments, but without applying new stain, resulting in six groups (n = 15): CtrII, CtrIV, SCII, SCIV, DCII, and DCIV. X-ray diffraction, color, translucency, and surface roughness analysis were also performed, and the samples were subjected to the biaxial flexural strength test. Data were subjected to one-way ANOVA, Tukey's test (α = 0.05), and Weibull analysis. Results: No changes in the diffractogram pattern were found, irrespective of the number of firings. The translucency (p = 0.02) and roughness (p < 0.01) of DCIV were significantly reduced compared to DCII. DCIV also showed the highest flexural strength (325.52AMPa), followed by SCII (271.64BMPa). Conclusions: Repeated firings increased the flexural strength of ZLS, where the double-step characterization technique demonstrated better statistical results than the other groups. Moreover, despite the ceramic showing good color stability, repeated firings significantly compromised its translucency.